Virtual Seminar: an innovative educational experience - Lina Maria Martinez-Sanchez; Yuban Sebastian Cuartas-Agudelo; Alejandro Hernandez-Martinez; Laura Herrera-Almanza; Miguel Saavedra-Valencia (Revista Internacional de Educação e Saúde, 2022)
INTRODUCTION: it is of special importance that teachers can easily transmit knowledge, using didactical tools such as Cmaptools, Slideshare, YouTube, among others. Because of that, teaching methods nowadays are going through a revolution that implies technological development and the arrival of new generations. OBJECTIVE: describe the experience of developing a virtual education strategy in our institution to improve the teaching and learning process and facilitate interaction with students. METHODOLOGY: the students must do a bibliography search in databases (PubMed, Science Direct, and Embase) choosing one recent (published within the previous 3 months) original article in English. The article must involve the use of molecular techniques that include some sort of electrophoresis, then, get a tutoring session with the main teacher of the course, after that, the student must design a PowerPoint slideshow of a maximum of 15 slides. Finally, must record a 10-minute-long video of the presentation, the video must be uploaded to the YouTube website. RESULTS: a greater comprehension of the seminar presentation dynamic was observed in comparison to the previous methodology, which did not include the virtual component. CONCLUSIONS: the implementation of new innovative methodologies in education allows students to develop a broader learning process, besides improving their scientific understanding; they improve their knowledge on technological tools implemented in education.